Perception of donor breast milk and determinants of its acceptability among mothers in a developing community: a cross-sectional multi-center study in south-east Nigeria - Kenechukwu K. Iloh; Chidiebere DI. Osuorah; Ikenna K. Ndu; Isaac N. Asinobi; Ijeoma N. Obumneme-Anyim; Chijioke E. Ezeudu; Ukoha M. Oluchi; Onyinye U. Anyanwu; Uchenna Ekwochi; Christian C. Ogoke; Adaeze C. Ayuk; Herbert U. Obu (BMC, 2018)
Abstract Background Due to the health and economic benefits of breast milk, the World Health Organization (WHO) recommends that for infants who cannot receive breast milk from their own mothers, the next preferred option is donated breast milk. This recommendation is however rarely practiced in most developing countries where donor milk is not widely accepted. Methods This cross-sectional multi-center study enrolled mothers attending antenatal or pediatric clinics in six tertiary institution in south-east Nigeria using purposive and convenient sampling method. Data collection was done using pretested questionnaires. The study aimed to assess the knowledge, acceptability and willingness to donate breast milk and/or use donated breast milk for their infants It also explored factors that determine this behavior. Results A total of 1235 mothers participated; 39% (480/1225) have heard about the concept of donor milk, while only 10% (79/759) and 7% (81/1179), respectively, had adequate knowledge of the concept and policy on donor milk. Sixty percent indicated willingness to use donor milk or donate breast milk if need arises. Respondents with lower age (p = 0.049) and with higher occupational status (p = 0.001) were more likely to have adequate knowledge of donor breast milk, while respondents with lower educational attainment (p = 0.002) and those who are non-Christians (p = 0.004) were more likely to request financial inducement for donating their breast milk. Adequate knowledge of the concept of donor milk (p = 0.001), preference of donor milk to infant formula (p = 0.001) and requirement of financial remuneration (p = 0.001) were the only significant predictors of willingness to donate and/or receive donated breast milk. Conclusion The knowledge of the concept of donor breast milk and awareness of policies regulating its practice in Nigeria is low, but the prospect of its acceptability is high among mothers surveyed in south-east Nigeria. Targeted public education by relevant government agencies in collaboration with clinicians, community and religious leaders about the concept of donor breast milk to families may help increase the acceptance and practice of donating breast milk and/or use of donated breast milk among mothers in the region.